-5(1-5)+(-8x-2)=4x-8x

Simple and best practice solution for -5(1-5)+(-8x-2)=4x-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(1-5)+(-8x-2)=4x-8x equation:


Simplifying
-5(1 + -5) + (-8x + -2) = 4x + -8x

Combine like terms: 1 + -5 = -4
-5(-4) + (-8x + -2) = 4x + -8x

Multiply -5 * -4
20 + (-8x + -2) = 4x + -8x

Reorder the terms:
20 + (-2 + -8x) = 4x + -8x

Remove parenthesis around (-2 + -8x)
20 + -2 + -8x = 4x + -8x

Combine like terms: 20 + -2 = 18
18 + -8x = 4x + -8x

Combine like terms: 4x + -8x = -4x
18 + -8x = -4x

Solving
18 + -8x = -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
18 + -8x + 4x = -4x + 4x

Combine like terms: -8x + 4x = -4x
18 + -4x = -4x + 4x

Combine like terms: -4x + 4x = 0
18 + -4x = 0

Add '-18' to each side of the equation.
18 + -18 + -4x = 0 + -18

Combine like terms: 18 + -18 = 0
0 + -4x = 0 + -18
-4x = 0 + -18

Combine like terms: 0 + -18 = -18
-4x = -18

Divide each side by '-4'.
x = 4.5

Simplifying
x = 4.5

See similar equations:

| -1/2+w=3/5 | | (x-6)+x= | | 23+2x=13 | | 3(2c+3)=2(3c-4) | | 6n-10+4n=-18+10n+14 | | 51-3x=6x+23 | | a+3b=7 | | 13+2x=x+25 | | 3x-18/15 | | 5=4n-6 | | 3w-40-2w+60+w= | | 13x+12=38 | | 4n-6=14 | | 15-12x=51 | | f(x)=10-4x | | 4x+18=x+33 | | -31/3b+b | | 8+6a=-28+24 | | 2(3.5x+6)=2.5x-2 | | 2=9x | | 1/2x+4=-3 | | 0.6x=-7.2 | | x^2+y^2-9= | | (x-3)(3x+5)=0 | | 3/4-1/2b=3b | | 7x+5=13x+5 | | -8z-7=3z-7+5z | | x^2+3x-6=7x+6 | | -18-6=(1+3x) | | 23x-29y=7 | | 5x^2(6x+2)= | | 4x^2+4xy^2+y^4= |

Equations solver categories